A renúncia de receita onerosa como política extrafiscal afirmativa do acesso à saúde - SILVA, Maria Stela Campos da (Universidade Federal do Pará, 2017)
This research involve financial legal, tax and administrative, especially with regard to public health policies. Based on the theory of the political philosophy of Amartya Sen's health, from the viewpoint that the state not only fulfills offer services to society, but must ensure that as many people as possible have access to such services that the fact comply with the needs of each; research, after enunciating the ways the state can waive tax revenue for through a policy extrafiscal attract second (companies) and the third (nonprofit corporations) society, identifies the legal forms that Brazil has been using since the last administrative reforms to attract the private sector to establish partnerships of various kinds for the alternative to him, offering more health for the population.At that stanchion the thesis raises some measures of internal and external control is exercised by organs that carry out these activities in Brazil, as the prosecutor, civil society, the Audit Courts to identify the key legal issues that these partnerships State and second and third sector face in the provision of health services.Finally, after a comparative analysis of structures with waiver of income on health in other countries , from research already undertaken in Brazil on certain species of resignation revenue for health, as studies of the Instituto de Pesquisa Econômica Aplicada (IPEA) and Regulatory Agencies area National Health (ANS) and National Health Surveillance Agency (ANVISA), correlating them to reports of analyzes of accounts of the federal government in recent years by the Court of Union, seeks to demonstrate the quantification of waivers in general revenue in relation to targeted health care to the end, suggesting to country implementation techniques that imply waiver of revenue in a mandatory direct consideration of the taxpayer benefited gaugeable the Public Entity.Thus,through exemptions costly attempts to demonstrate the possibility of circumventing the problems better legal waivers of free prescriptions in favor of increasing the distribution of health services in a more qualitative.